Clinical Efficacy of Endoscopic Submucosal Dissection for Adenocarcinomas of the Esophagogastric Junction - Nagami, Yasuaki; Machida, Hirohisa; Shiba, Masatsugu; Obayashi, Tomoko; Ominami, Masaki; Fukunaga, Shusei; Sugimori, Satoshi; Yamagami, Hirokazu; Tanigawa, Tetsuya; Watanabe, Kenji; Watanabe, Toshio; Tominaga, Kazunari; Fujiwara, Yasuhiro; Arakawa, Tetsuo (Endoscopy International Open, 2014)
Background and Study Aims There are a few reports about the efficacy of endoscopic submucosal dissection (ESD) for adenocarcinomas of the esophagogastric junction (EGJ). However, there is no detailed analysis that divides EGJ cancers into Barrett’s adenocarcinoma and gastric cardia adenocarcinoma. The aim of this study was to analyze the efficacy of ESD for EGJ cancers, comparing these two adenocarcinomas.Patients and Methods This study included 43 patients who underwent ESD for type II EGJ cancers between 2004 and 2011. Pathological examination of resected specimens confirmed 14 cases of Barrett’s adenocarcinoma and 29 cases of gastric cardia adenocarcinoma. Cutting margins on the oral side were placed 1 cm from the squamocolumnar junction, or 1 cm away from the slight elevation that is an endoscopic sign of subsquamous carcinoma extension. Clinical outcomes, prevalence and length of subsquamous carcinoma extension, and long-term outcomes were compared between these two types of adenocarcinoma.Results No significant differences in clinical outcomes were found between these two types of adenocarcinoma (en bloc, 100 % versus 100 %; complete, 100 % versus 89.7 %; curative, 85.7 % versus 75.9 %). No serious adverse events were encountered. The prevalence of subsquamous carcinoma extension was significantly higher in Barrett’s adenocarcinoma compared with gastric cardia adenocarcinoma. Local and distant recurrence were not observed in any cases with curative resection during the follow-up period (1.6 – 87.6 months).Conclusion ESD for EGJ cancers, including both Barrett’s adenocarcinoma and gastric cardia adenocarcinoma, was efficient and useful. ESD with a 1 cm safety margin may be acceptable for EGJ cancers.